Improving Oral and Dental Healthcare Quality Management to Enhance Patient Satisfaction in Hospitals: A Systematic Literature Review - Ayu Kezia Walean; Vip Paramarta; Kosasih Kosasih; Farida Yuliaty (Jurnal Pengabdian Nusantara, 2026)
The quality of dental and oral health services is a crucial component in enhancing hospital service quality, as it directly impacts patient experience, trust, and satisfaction. Effective quality management is essential to ensure that services are safe, effective, timely, patient-oriented, and aligned with professional standards. This study aims to analyze and synthesize scientific evidence regarding the implementation of quality management in dental and oral health services and its impact on increasing patient satisfaction in hospitals. A Systematic Literature Review (SLR) design utilizing the PRISMA approach was employed. Literature was obtained through searches of scientific databases using keywords related to dental and oral health services, quality management, service quality, patient satisfaction, and hospitals. Selected articles consisted of quantitative studies addressing dental and oral health service quality and patient satisfaction, published within the researcher-defined timeframe, and available in full text. The selection process was based on inclusion and exclusion criteria; subsequently, data were extracted, assessed for methodological quality, and narratively synthesized. The synthesis indicates that improvements in dental and oral health service quality management are associated with increased patient satisfaction. Consistently contributing factors include service reliability, healthcare worker responsiveness, professional assurance and competence, empathy, effective communication, facility availability, environmental cleanliness, waiting times, and ease of access. Key strategies for enhancing patient experience include implementing quality standards, conducting periodic satisfaction evaluations, strengthening healthcare worker competence, and pursuing continuous improvement. In conclusion, integrated and patient-oriented quality management plays a vital role in boosting patient satisfaction with hospital-based dental and oral health services. Strengthening quality evaluation systems and continuous quality improvement efforts is essential to ensure the delivery of safe, effective, responsive, and patient-centered care.